1979
DOI: 10.1002/jez.1402090206
|View full text |Cite
|
Sign up to set email alerts
|

Germinal vesicle configurations and patterns of polypeptide synthesis of porcine oocytes from antral follicles of different size, as related to their competency for spontaneous maturation

Abstract: The cytogenetic configurations of germinal vesicle (gv) chromatin were analyzed for pools of porcine oocytes harvested from small (1.0-2.0 mm), medium (3.0-5.0 mm), and large (6.0-10.0 mm) antral follicles. Groups of oocytes from these follicular classes also were examined by high-resolution, two-dimensional, polyacrylamide gel electrophoresis to compare their patterns of polypeptide synthesis. The results show a high incidence of gross and cytogenetic degeneration among oocytes from small antral follicles as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 33 publications
3
32
2
Order By: Relevance
“…Evidence suggests that the persistence of interphase characteristics in incompetent oocytes (Wickramasinghe et al, 1990) is due either to the lack of expression of certain cell cycle proteins required for meiotic competence, or the absence of posttranslational modifications that are required for their activity. In support of this hypothesis, incompetent oocytes show very different patterns of both polypeptide synthesis (McGaughey et al, 1979) and protein phosphorylation (Bornslaeger et al, 1988) compared with their competent counterparts. Moreover, although some MPF proteins are present in meiotically incompetent growing pig oocytes, they are incapable of being activated until the oocyte is fully grown (Christmann et al, 1993).…”
Section: Cell Cycle Proteins and Meiosismentioning
confidence: 83%
See 1 more Smart Citation
“…Evidence suggests that the persistence of interphase characteristics in incompetent oocytes (Wickramasinghe et al, 1990) is due either to the lack of expression of certain cell cycle proteins required for meiotic competence, or the absence of posttranslational modifications that are required for their activity. In support of this hypothesis, incompetent oocytes show very different patterns of both polypeptide synthesis (McGaughey et al, 1979) and protein phosphorylation (Bornslaeger et al, 1988) compared with their competent counterparts. Moreover, although some MPF proteins are present in meiotically incompetent growing pig oocytes, they are incapable of being activated until the oocyte is fully grown (Christmann et al, 1993).…”
Section: Cell Cycle Proteins and Meiosismentioning
confidence: 83%
“…However, protein patterns clearly change with time during oocyte development well before the oocyte is fully grown and appear to be species-specific. Competency to undergo meiotic maturation, which is acquired during follicular development, is correlated with distinct changes in protein patterns in both mouse (Sorenson and Wassarman, 1976) and pig (McGaughey et al, 1979) oocytes. Since oocytes from small preantral follicles are not meiotically competent, it seems reasonable to assume that protein synthesis aRer this stage of development but before the oocytes are fully grown may be prerequisite for GVBD.…”
Section: Cell Cycle Proteins and Meiosismentioning
confidence: 99%
“…Whatever the follicle quality, the zonae pellucidae of GV1 oocytes were never absent and showed normal morphology in more than 80% of cases studied. In healthy follicles, normal zonae pellucidae were more often observed around GV2 (Mandl, 1962), pig (McGaughey et al, 1979;Daguet, 1980), macaque (Thibault, 1974) and humans (Tesarik et al, 1983;Gougeon & Testart, 1986 (Hunter & Polge, 1966;Himelstein-Braw et al, 1976;Motlik & Fulka, 1976;Daguet, 1980;Gougeon, 1981;Thibault et al, 1987). Our results are in agreement with these observations, since we have observed a significant relationship between nuclear changes and germinal vesicle position in healthy follicles : the frequency of peripheral GV was higher in GV3 oocytes compared to GV1 (P < 0.001 ) and GV2 oocytes (P < 0.001 However, in a few cases GV migration occurred even in the GV1 oocyte.…”
Section: Animals and Samplingmentioning
confidence: 99%
“…A large variation in nuclear morphology of GV stage pig oocytes was found just after collection (Funahashi et al, 1997a;Nagai et al, 1997) and after a certain time of culture (Funahashi et al, 1997a). It has been shown that there are differences in GV configuration and polypeptide synthesis between oocytes obtained from different size antral follicles causing heterogeneity in overall developmental competence within oocytes, collected for IVM/IVF (Mcgaughey et al, 1979). Since the source of oocytes may differ (from different individuals and different size follicles), the developmental competence of GV stage pig oocytes used for IVM/IVF can also vary within the population used in one experiment.…”
Section: Importance Of Meiotic Synchronisation During In Vitro Maturamentioning
confidence: 99%